The Role of Biobanks in Oncology Research – A Portuguese Perspective - Gomes, Mónica; Teixeira, Ana Luísa; Coelho, Ana; Medeiros, Rui; Araújo, António (Journal of Intellectual Disability - Diagnosis and Treatment, 2015)
Approximately, 14.1 million new cancer cases and 8.2 million deaths occurred in 2012 worldwide. Cancer is a group of diseases characterized by uncontrolled growth, spread of abnormal cells and is a leading cause of death in both more and less economically developed countries. The growth in our knowledge of cancer biology has led to remarkable progress in cancer prevention, early detection and treatment. Recent years have seen a remarkable progress in the basic, translational and clinical research in cancers. During carcinogenesis several genetic and epigenetic alterations occur and a molecular approach based on the detection of these molecular alterations can permit the definition of molecular signatures specific for different tumors, allowing the definition of molecular biomarkers. These markers can be found in a variety of fluids, tissues and cell lines, and can be used for screening the general population, for differential diagnosis in symptomatic patients and for clinical staging of cancer. Furthermore, the biomarkers can be used to evaluate response to treatment, to assess disease recurrence through monitoring and as prognostic indicators of disease progression. The advances in the molecular knowledge and technology from research is based on the study of different types of biological samples, being necessary the collection, processing, preservation, stored and maintenance of these samples required an ordered and structured plan with the consequent creation of a biobank. The promotion and operation of biobanks provide to scientists the opportunity to access to quality samples and associated data, representing an essential milestone in shortening the time between research and clinical application, improving the effectiveness of research.